A qualitative study exploring perspectives towards rational use of medicines in Pakistan’s Malaria Control Program (MCP) - Malik, Madeeha; Hassali, Mohamed Azmi; Shafie, Asrul Akmal; Hussain, Azhar (Universidade de São Paulo, 2013)
Malaria is one of the most important global public health problems threatening the health of the population owing to prevailing socio-economic conditions and epidemiological reasons in Pakistan. This qualitative study has focused on the perspectives held towards the rational use of medicine intervention among malaria control program officials. Eight semi-structured interviews with all officials working for the malaria control program in Islamabad were conducted. The interviews, which were audio-taped and transcribed verbatim, were evaluated by thematic content analysis and by all authors. All respondents agreed on successful implementation of the malaria control program in Pakistan for controlling malaria by improving diagnostic and treatment facilities and promoting rational case management through training of prescribers. However, funding is still the major challenge faced by the program for its future implementation.